El recurso de apelación en el Código General del Proceso: un desatino para la justicia colombiana - Quintero González, Armando (2015)
Not only the search of decongest the administration of justice was the engine of the creationof the General Procedural Code. The society is evolving according to its needs, that includeeconomic, social, cultural and also technological needs, thus it should be understood thatthe law is not static, and that must make huge strides to keep up with social changes,consequently it should advance at pace in accordance with humanity requirements.Accordingly, this article will perform an approximation to the study and evolution of theappeal procedure seen from the General Procedural Code where comes into view a conflictbetween material satisfaction of the rights of the citizens or effective judicial protectionwith the appeal procedure currently characterized as restricted.